Desain dan Pengembangan Sistem Informasi Manajemen Proyek Berbasis Web di Apotek Cemara - Fikri Darojatul Ilmi; Purnomo Sidiq (Jurnal Ilmu Komputer dan Sistem Informasi, 2026)
Project management at Cemara Pharmacy faced challenges such as poor team coordination, progress monitoring difficulties, and data inaccuracies, hindering operational efficiency in the pharmaceutical sector. This study aimed to design and develop a web-based project management information system to support real-time planning, execution, and evaluation of projects. The research employed the Waterfall model, with data collection via field observations, interviews with managers and staff, document analysis, and literature review; the population comprised Cemara Pharmacy staff as primary participants, using UML (Use Case, Activity, Sequence, Class Diagrams), WBS, Gantt Chart, and PERT as instruments; data analysis involved functional, integration, and User Acceptance Testing (UAT). Results demonstrated that the Laravel- and MySQL-based system enhanced transparency, reduced administrative errors, and improved efficiency by up to 30%, with user evaluations highlighting interface ease and multi-platform accessibility. The study concludes that the system significantly contributes to professional project management in pharmacy SMEs, implying broader operational digital transformation.